Examining the effects of screen time on language development: A university-based study in Hanoi, Vietnam - Le, Dung; Huong, Tran Nho; Chi, Pham Linh (Journal of Language, Literature, Social and Cultural Studies, 2025)
This study investigates the self-perceived impact of screen use on language skills among university students across four disciplines: business, technology, healthcare, and humanity and languages. Quantitative analysis revealed significant differences in perceived impact, with healthcare students reporting the highest levels of benefit, followed by humanity and languages, business, and technology students. Focus group discussions with a subset of 30 students provided qualitative insights, highlighting varying patterns of screen use across three categories: low, moderate, and high screen time users. Low screen time users preferred traditional learning methods and expressed scepticism about the effectiveness of screens. Moderate users leveraged screens as a complementary tool for language practice, while high users perceived transformative benefits, particularly in pronunciation, vocabulary, and fluency, despite challenges such as distractions and physical strain. The findings underscore the need for tailored strategies to optimize screen use, taking into account discipline-specific practices and individual screen time habits. This study contributes to understanding the role of digital tools in language learning and offers practical recommendations for integrating screen use effectively in educational contexts.